Analysis of pig serum proteins based on shotgun liquid chromatography-tandem mass spectrometry - Xiangtao Liu; Keshan Zhang, Yongjie Liu, Youjun Shang, Haixue Zheng, Jianhong Guo, Hong Tian, Ye Jin, Jijun He (African Journal of Pig Farming, 2019)
Recent advances in proteomics technologies have opened up significant opportunities for future applications. We used shotgun liquid chromatography, coupled with tandem mass spectrometry (LC-MS/MS) to determine the proteome profile of healthy pig serum. Samples of venous blood were collected and subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis separation and in-gel trypsin digestion. The peptides were then processed using shotgun LC-MS/MS. Serum proteins were subjected to protein identification and bioinformatics analysis. A total of 392 proteins were identified, and 179 were annotated according to their molecular functions and biological processes, excluding 142 hypothetical proteins and 71 immune globulins. To the best of our knowledge, this represents the first porcine serum proteomics analysis based on shotgun LC-MS/MS. This method and the resulting proteomics information may prove valuable for ensuring good animal welfare practice and for monitoring swine health and disease status.